THE EFFECT OF FARMERS’ MOTIVATION ON WILLINGNESS TO CONTINUE ORGANIC FARMING IN BANTUL, INDONESIA - Arum, Mutiarra Ridyo; Arbianti, Arbianti; Hikmah, Maulia (Universitas Islam Kadiri, 2025)
Bantul Regency is one of the central areas of organic farming in the Daerah Istimewa Yogyakarta Province. However, its development has slowed down and often ends with a switch back to conventional farming systems. This study aims to determine how motivation influences the willingness to continue (WTC) to continue organic farming in Bantul Regency. The location in Bantul Regency was purposively selected based on the potential for organic farming development, using non-probability techniques we used questionnaires to collect data among 42 participants and in-depth interviews with three key informants. The ERG theory is used as an approach to complement three important variables, namely existence, relatedness, and growth, then analysed using PLS-SEM. These findings indicate that farmers' decisions to continue (WTC) organic farming are influenced not only by fulfilling basic needs or incentives (existence) but also by their psychosocial drive (growth). Meanwhile, external influences (relatedness) are not significant in motivating farmers to sustain organic farming practices. Therefore, the government should look after individual drives more than other factors and start to improve their service performance to give a better impression towards the farmers for support the success of organic farming